Metabolic Effects of Social Isolation in Adult C57BL/6 Mice. (26th November 2014) - Sun, Meng; Choi, Eugene Y.; Magee, Daniel J.; Stets, Colin W.; During, Matthew J.; Lin, En-Ju D.
Abstract : Obesity and metabolic dysfunction are risk factors for a number of chronic diseases, such as type 2 diabetes, hypertension, heart disease, stroke, and certain forms of cancers. Both animal studies and human population-based and clinical studies have suggested that chronic stress is a risk factor for metabolic disorders. A good social support system is known to exert positive effects on the mental and physical well-being of an individual. On the other hand, long-term deprivation of social contacts may represent a stressful condition that has negative effects on health. In the present study, we investigated the effects of chronic social isolation on metabolic parameters in adult C57BL/6 mice. We found that individually housed mice had increased adipose mass compared to group-housed mice, despite comparable body weight. The mechanism for the expansion of white adipose tissue mass was depot-specific. Notably, food intake was reduced in the social isolated animals, which occurred around the light-dark phase transition periods. Similarly, reductions in heat generated and the respiratory exchange ratio were observed during the light-dark transitions. These phase-specific changes due to long-term social isolation have not been reported previously. Our study shows social isolation contributes to increased adiposity and altered metabolic functions.